Determinants of Net Income of Growth in Manufacturing Companies: Evidence in Emerging Markets - Anita Putri (Yayasan Multidimensi Kreatif, 2025)
The purpose of this study is to identify the variables influencing earnings growth. Profitability, liquidity, and firm size are the variables examined in manufacturing firms in the basic and chemical industries listed on the Indonesia Stock Exchange between 2019 and 2023. 37 businesses served as the study's samples. Multiple linear regression models and secondary data processed with SPSS 24.0 were used in this investigation. The findings demonstrated that net profit growth was negatively and significantly impacted by profitability, liquidity, and company size.